2019
DOI: 10.1111/1744-9987.13350
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Direct‐Acting Antiviral Therapy for Renal Function in Post‐Kidney Transplant Patients Infected with Hepatitis C Virus and a 100% 12‐Week Sustained Virologic Response: A Single‐Center Study

Abstract: Treatment of chronic hepatitis C infection after renal transplantation has been controversial due to the high rate of graft rejections with interferon (IFN)‐based therapies. The aim of this study is to review our experience of direct acting antiviral therapy for the recipients of renal transplantation. Eleven recipients who were hepatitis C virus‐polymerase chain reaction (PCR) positive were eligible for the treatment with direct acting antivirals. Six recipients were treated with sofosbuvir and ledipasvir, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Currently, only few studies in the literature, most of which included relatively small numbers of patients, have focused on KT recipients with CHC treated with DAAs (Table 4) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. (Table 4) that DAAs are highly effective in KT recipients, offering SVR rates comparable to those achieved in the non-transplant setting and therefore representing major progress in the elimination of HCV infection in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, only few studies in the literature, most of which included relatively small numbers of patients, have focused on KT recipients with CHC treated with DAAs (Table 4) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. (Table 4) that DAAs are highly effective in KT recipients, offering SVR rates comparable to those achieved in the non-transplant setting and therefore representing major progress in the elimination of HCV infection in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Although significant treatment success has been achieved in non‐kidney transplant patients, the success rate for DAA therapy in kidney transplant recipients has varied from 89% to 100% 11,18–24 . Colombo et al 25 performed a phase 2 randomized trial involving kidney transplant recipients treated with DAA and reported SVR rates of 100% and 96% at 3 and 6 months, respectively.…”
Section: Discussionmentioning
confidence: 99%